First year on commercial hybrid closed‐loop system—experience on 111 children and adolescents with type 1 diabetes. Issue 6 (28th May 2021) - Varimo, Tero; Pulkkinen, Mari‐Anne; Hakonen, Elina; Hero, Matti; Miettinen, Päivi J.; Tuomaala, Anna‐Kaisa
Abstract: Objective: The hybrid close‐loop system (HCL) is a rapidly emerging treatment method for type 1 diabetes (T1D), but the long‐term effectiveness of the system remains unclear. This study investigates the influence of the HCL on glycemic control in children and adolescents with T1D in a real‐life setting during the first year on HCL. Research design and methods: This retrospective study included all the patients (n = 111) aged 3 to 16 years with T1D who initiated the HCL system between 1st of December 2018 and 1st of December 2019 in the Helsinki University Hospital. Time in range (TIR), HbA1c, mean sensor glucose (SG) value, time below range (TBR), and SG coefficient of variance (CV) were measured at 0, 1, 3, 6, and 12 month. The changes over time were analyzed with a repeated mixed model adjusted with baseline glycemic control. Results: After the initiation of HCL, all measures of glycemic control, except HbA1c, improved and the effect lasted throughout the study period. Between 0 and 12 month, TIR increased (β = −2.5 [95%CI: −3.6 − (−1.3)], p < 0.001), whereas mean SG values (β = −0.7 [95%CI: −0.9 − (−0.4)]), TBR (β = −2.5 [95%CI: −3.6 − (−1.3)]), and SG CV (β = −4.5 [95%CI: −6.3 − [−2.8]) decreased significantly ( p < 0.001). Importantly, the changes occurred regardless of the age of the patient. Conclusions: Measurements of glycemic control, except HbA1c, improved significantly after the initiation of the HCL system and the favorable effect lasted throughout the follow‐up. These results support the view that HCL is an efficacious treatment modality for children and adolescents with T1D of all ages.